Stigma management as celebration: disability, difference, and the marketing of diversity. Issue 4 (7th August 2020) - Low, Jacqueline
Abstract : In this paper, I present a celebration of diversity as a new form of stigma management based on a qualitative analysis of media images of disabled bodies in fashion shows, advertising, and other marketing campaigns. In making my arguments I am chiefly concerned with modes of stigma management appropriate to discrediting stigma, stigma that cannot be concealed and must be managed if the individual is not to suffer the punitive reactions of others. To date, modes of stigma management conceptualise the disabled body in a negative manner. In covering attention must be distracted from the disability, whereas disclosing is meant to defuse what is fearful or frustrating about the disability, and finally, in deviance disavowal and challenging the negative attributes of disability must be transcended or transferred. I argue that celebration of diversity is different as it does not conceptualise the disabled body in a negative way but rather reflects the normalisation of disabled bodies in contemporary culture, a key attribute of which is the valuing of diversity.